2020
DOI: 10.1007/s10456-020-09748-4
|View full text |Cite
|
Sign up to set email alerts
|

BMP6/TAZ-Hippo signaling modulates angiogenesis and endothelial cell response to VEGF

Abstract: The BMP/TGFβ-Smad, Notch and VEGF signaling guides formation of endothelial tip and stalk cells. However, the crosstalk of bone morphogenetic proteins (BMPs) and vascular endothelial growth factor receptor 2 (VEGFR2) signaling has remained largely unknown. We demonstrate that BMP family members regulate VEGFR2 and Notch signaling, and act via TAZ-Hippo signaling pathway. BMPs were found to be regulated after VEGF gene transfer in C57/Bl6 mice and in a porcine myocardial ischemia model. BMPs 2/4/6 were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 75 publications
1
91
0
Order By: Relevance
“…The Hippo pathway has emerged as an important upstream signaling pathway in angiogenesis [53]. In detail, TAZ has been reported to be involved in VEGF-induced endothelial cell sprouting [54]. In addition, TAZ also enhances angiogenesis in EGFR wild-type non-small cell lung cancer cells [55].…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo pathway has emerged as an important upstream signaling pathway in angiogenesis [53]. In detail, TAZ has been reported to be involved in VEGF-induced endothelial cell sprouting [54]. In addition, TAZ also enhances angiogenesis in EGFR wild-type non-small cell lung cancer cells [55].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Notch renders the responsiveness of ECs toward pro-angiogenic BMP stimuli, BMP2 and BMP6, by regulating the expression of SMAD6, which ultimately contributes to the phosphorylation of SMAD1/5 and a tip cell phenotype (Mouillesseaux et al, 2016). Recent findings also implicated synergistic effects of BMP signaling and VEGF signaling on tip cell-associated markers VEGFR2 and DLL4 (Pulkkinen et al, 2020). Furthermore, Notch signaling also appears to influence BMP signaling at the effector level since the expression of Herp2 in ECs is co-modulated by Notch and BMP6 signaling (Itoh et al, 2004).…”
Section: Endothelial Heterogeneity and Bmp Signalingmentioning
confidence: 99%
“…In addition to mechanical forces, recent studies reported hypoxia as one of the potential modulators for BMP signaling. Under hypoxic conditions, differential expression of BMP ligands could be observed in comparison to normoxic conditions ( Pulkkinen et al, 2021 ). Moreover, BMP signaling could also attenuate hypoxic responses in ECs through the ALK1/SMAD/ATOH8 axis, ultimately impeding the development of pulmonary arterial hypertension (PAH) ( Morikawa et al, 2019 ).…”
Section: Factors That Modify Cellular Outcomes Of Bmp Signalingmentioning
confidence: 99%
“…In the circulatory system, numerous cooperation between VEGF signaling and BMP signaling have been reported (Figure 2; number 7). For instance, BMP2/6/9, but also Bmper and Endoglin, are all induced by VEGF in the endothelium, in vitro and in vivo [180]. Conversely, the development of the outflow tract in the mouse heart is controlled by BMP4/7-SMAD-mediated direct and indirect repression of Vegf-a [181].…”
Section: Interplay Between Bmp and Vegf Signalingmentioning
confidence: 99%
“…Indeed, the pro-angiogenic activity of BMP4 in HUVECs is mediated by a BMPRII-mediated intracellular transactivation of VEGFR2 via c-Src [183]. Recently, Pulkkinen et al showed through in vitro and in vivo studies that BMP2, but also BMP6, signaling causes VEGFR2-mediated vessel sprouting [180].…”
Section: Interplay Between Bmp and Vegf Signalingmentioning
confidence: 99%